Large-Margin Discriminative Training of Hidden Markov Models for Speech Recognition (invited) - Yu, Dong; Deng, Li (Proc. IEEE Intern. Conf. Semantic Computing, Irvine, CA, 2007)
Discriminative training has been a leading factor for improving automatic speech recognition (ASR) performance over the last decade. The traditional discriminative training, however, has been aimed to minimize empirical error rates on training sets, which may not be well generalized to test sets. Many attempts have been made recently to incorporate the principle of large margin (PLM) into the training of hidden Markov models (HMMs) in ASR to improve the generalization abilities. Significant error rate reduction on the test sets has been observed on both small vocabulary and large vocabulary continuous ASR tasks using large-margin discriminative training (LMDT) techniques. In this paper, we introduce the PLM, define the concept of margin in the HMMs, and survey a number of popular LMDT algorithms proposed and developed recently. Specifically, we review and compare the large-margin minimum classification error (LM-MCE) estimation, soft-margin estimation (SME), large margin estimation (LME), large relative margin estimation (LRME), and large margin training (LMT) with a focus on the insights, the training criteria, the optimization techniques used, and the strengths and weaknesses of these different approaches. We suggest future research directions in our conclusion of this paper.